CHANGES IN THE LEVEL OF OXYPROLINE IN WOMEN OF REPRODUCTIVE AGE WITH PROLAPSE OF THE GENITALS - Saijalilova Dilnoza; Urinova Rozagul (Scholar Express Journals, 2023)
83 women of reproductive age were examined, of which 63 women had genital prolapse. In 57.1% of women with PH, nCTD was detected . The severity of PG depended on the severity of UCTD . The study of the level of hydroxyproline in the urine revealed in most women with PH its increased excretion, which reflected an enhanced process of collagen catabolism. At present, the theory of systemic connective tissue dysplasia as the leading cause of prolapses has become widespread.
Keywords: Genital prolapse; connective tissue dysplasia; hydroxyproline